2017
DOI: 10.1016/j.chemgeo.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry, geothermometry and influence of the concentration of mobile elements in the chemical characteristics of carbonate-evaporitic thermal systems. The case of the Tiermas geothermal system (Spain)

Abstract: The Tiermas low temperature geothermal system, hosted in the Paleocene-Eocene carbonates of the Jaca-Pamplona basin, has been studied to evaluate the geochemistry and the temperature of the waters in the deep reservoir. These waters are of chloridesodium type and emerge with a temperature of about 37 ºC. Two hydrogeochemical groups of waters have been distinguished: one with lower sulphate concentration and lower TDS (about 7,500 ppm) and the other with higher sulphate content and TDS values (close to 11,000 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 59 publications
3
13
0
Order By: Relevance
“…These geothermometers have provided coherent results in some systems similar to the ones studied here (e.g. Apollaro et al, 2012;Blasco et al, 2018Blasco et al, , 2017Fernández et al, 1988;Gökgöz and Tarkan, 2006;Michard and Bastide, 1988;Mohammadi et al, 2010;Pastorelli et al, 1999;Wang et al, 2015) and, therefore, their applicability in the Fitero -Arnedillo geothermal system is tested. Classical chemical geothermometers and calibrations used in this study are:…”
Section: Chemical Geothermometerssupporting
confidence: 60%
See 3 more Smart Citations
“…These geothermometers have provided coherent results in some systems similar to the ones studied here (e.g. Apollaro et al, 2012;Blasco et al, 2018Blasco et al, , 2017Fernández et al, 1988;Gökgöz and Tarkan, 2006;Michard and Bastide, 1988;Mohammadi et al, 2010;Pastorelli et al, 1999;Wang et al, 2015) and, therefore, their applicability in the Fitero -Arnedillo geothermal system is tested. Classical chemical geothermometers and calibrations used in this study are:…”
Section: Chemical Geothermometerssupporting
confidence: 60%
“…The temperatures obtained with this last calibration (CaSO4-H2O exchange) are the most reasonable ones since anhydrite is in equilibrium in the system (see below) and, they are in the range previously defined with the chemical geothermometers. The bad results obtained with the calibration based on SO4 2-(despite being the dominant sulphur species in this type of waters), are probably due to the lack of equilibrium between SO4 2and H2O (Blasco et al, 2018(Blasco et al, , 2017Boschetti et al, 2011). On the contrary, although, the HSO4 is not the main species, the calibration based on it provides good results because it is very similar to the CaSO4-H2O calibration in a 10 3 lnα -10 6 /T 2 plot (see Blasco et al, 2018).…”
Section: The Calibration Based On the Equilibrium Exchange Between Anmentioning
confidence: 89%
See 2 more Smart Citations
“…The ion charge imbalances for the water samples were calculated using the program AquaChem, and the results showed that all of the samples have a charge imbalance less than ±5% (Table 1). Values in this range are usually accepted as valid and can support the reliability of the data used in this work [25][26][27].…”
Section: Methodsmentioning
confidence: 73%